2001
DOI: 10.1074/jbc.m101906200
|View full text |Cite
|
Sign up to set email alerts
|

Osmolytes Stabilize Ribonuclease S by Stabilizing Its Fragments S Protein and S Peptide to Compact Folding-competent States

Abstract: Osmolytes stabilize proteins to thermal and chemical denaturation. We have studied the effects of the osmolytes sarcosine, betaine, trimethylamine-N-oxide, and taurine on the structure and stability of the protein⅐peptide complex RNase S using x-ray crystallography and titration calorimetry, respectively. The largest degree of stabilization is achieved with 6 M sarcosine, which increases the denaturation temperatures of RNase S and S pro by 24.6 and 17.4°C, respectively, at pH 5 and protects both proteins agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 58 publications
(112 reference statements)
11
32
0
Order By: Relevance
“…One of the important conclusions reached from the results presented in Table I is that TMAO stabilizes proteins if pH is Ն5.0 and destabilizes proteins if pH is Ͻ5.0. It is noteworthy that our findings at pH 5.0 and above is consistent with earlier reports (7)(8)(9)(10)(11)36). However, no report is available for the effect of TMAO on protein stability at pH values of Ͻ5.0.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…One of the important conclusions reached from the results presented in Table I is that TMAO stabilizes proteins if pH is Ն5.0 and destabilizes proteins if pH is Ͻ5.0. It is noteworthy that our findings at pH 5.0 and above is consistent with earlier reports (7)(8)(9)(10)(11)36). However, no report is available for the effect of TMAO on protein stability at pH values of Ͻ5.0.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that the structure of the native and denatured states of proteins are not affected in the presence of TMAO (7,26). The results shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies have neglected the possibility that the presence of osmolytes would change the protein structure, especially the unfolded state as indicated here and in other studies. 12,[33][34][35]37,42,50 Reasoning according to the new view of protein folding based on funnels or energy landscapes, 51 the conformational space accessible to the unfolded state decreases in the presence of osmolytes when the unfolded state acquires residual native interactions that channel the folding of the protein. Osmolytes may channel folding along particular pathways by preferentially stabilizing one or more structural components of an ensemble.…”
mentioning
confidence: 99%
“…For example, cartilaginous fish concentrate trimethylamine N-oxide (TMAO), to offset the damaging effects of urea on protein function, and it is one of the best studied protecting osmolytes (e.g. 16 -20).The mechanisms by which protecting osmolytes promote protein folding, increase protein stability, and induce conformational changes have been the focus of intense investigation (15,18,19,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). However, nothing is known about the effects of denaturing or protecting osmolytes on the mechanical properties of PKD domains.…”
mentioning
confidence: 99%